Inequalities in the use of health services by adults and elderly people with and without noncommunicable diseases in Brazil, 2019 National Health Survey - Deborah Carvalho Malta; Regina Tomie Ivata Bernal; Crizian Saar Gomes; Laís Santos de Magalhães Cardoso; Margareth Guimarães Lima; Marilisa Berti de Azevedo Barros
ABSTRACT: Objective: The objective of this study was to investigate the use of health services and limitations in performing usual activities by adults and elderly people with and without noncommunicable chronic diseases (NCDs), according to sociodemographic strata. Methods: This is a cross-sectional study in which data from the 2019 National Health Survey were analyzed. The final sample corresponded to 88,531 households with interviews carried out, referring to individuals aged 18 years and above. The prevalence of use of services by the population with NCDs was compared with that of the population without NCDs and stratified by socioeconomic and demographic variables. Prevalence ratios (PRs) and 95% confidence intervals (95%CI) were calculated. Results: In 2019, 47.6% (95%CI 47.0-48.3) of the population reported having one or more NCDs. Population with NCDs had more medical consultations in the last 12 months (adjusted PR [APR]=1.21; 95%CI 1.20-1.23), used more health services in the last 2 weeks (APR=2.01; 95%CI 1.91-2.11), were referred to more hospitalization (APR=2.11; 95%CI 1.89-2.36), and had more limitations in performing usual activities (APR=2.52; 95%CI 2.30-2.76), compared with the population without NCDs. A positive dose-response gradient was observed between the number of comorbidities and the use of services. In all socioeconomic and demographic strata, the prevalence of indicators was higher in people with NCDs. Conclusion: The presence of NCDs was associated with a higher frequency of use of health services (i.e., consultation, use of services, and hospitalization) and the restriction of usual activities in all socioeconomic and demographic strata.